Integration of PjBL-STEM in IPAS Learning: An Effort to Stimulate Creative Thinking and Sustainability Awareness in Elementary Schools - Risnawati Risnawati; Didit Ardianto; Anna Permanasari (MASI Mandiri Edukasi, 2026)
Twenty-first-century education requires learning that is not only oriented toward conceptual mastery but also able to stimulate students’ creative thinking skills and sustainability awareness. However, previous studies have mostly examined PjBL-STEM separately in relation to learning outcomes or creative thinking, while research integrating PjBL-STEM into IPAS learning to stimulate both creative thinking and sustainability awareness remains limited. This study aims to examine the integration of Project-Based Learning with the Science, Technology, Engineering, and Mathematics approach (PjBL-STEM) in IPAS learning to stimulate elementary school students’ creative thinking skills and sustainability awareness. This study employed a quantitative, quasi-experimental design with a pretest-posttest control group. The research subjects were 45 sixth-grade students from SD Negeri 1 Cisaat, comprising 24 in the experimental class and 21 in the control class. The research instruments included a creative thinking skills test, a sustainability awareness questionnaire, and a learning implementation observation sheet. The data were analyzed using N-Gain and t-test with the assistance of IBM SPSS Statistics 25. The results showed that PjBL-STEM implementation reached 100%, indicating that all learning stages were carried out according to the designed syntax. Students’ creative thinking skills in the experimental class increased from a mean score of 45.04 to 72.79, with an N-Gain of 0.65 in the moderate category, while the control class obtained an N-Gain of 0.29 in the low category. Students’ sustainability awareness reached 96.20%, which was categorized as very strong. Therefore, integrating PjBL-STEM into IPAS learning effectively stimulates elementary school students’ creative thinking skills and sustainability awareness. This study implies that teachers can use PjBL-STEM as a contextual learning strategy to connect IPAS concepts with real environmental problems and sustainability-oriented project activities.